Determination of future prevention strategies in elite track and field: analysis of Daegu 2011 IAAF Championships injuries and illnesses surveillance - Alonso, J. M.; Edouard, P.; Fischetto, G.; Adams, B.; Depiesse, F.; Mountjoy, M. (British Journal of Sports Medicine, 2012)
Objective To determine the incidence and characteristics of newly incurred injuries and illnesses during international Athletics Championships, by improving the medical surveillance coverage, in order to determine future prevention strategies.